Electron transitions in a Ce(iii)-catecholate metal–organic framework. Issue 4 (15th December 2021) - Knapp, Julia G.; Ray, Debmalya; Calio, Paul B.; Wasson, Megan C.; Scott, Thais R.; Gagliardi, Laura; Farha, Omar K.
Abstract : Competitive electron transitions are present in a rare three-dimensional Ce(iii )-catecholate metal–organic framework. Abstract : A rare three-dimensional catecholate-based Ce(iii ) metal–organic framework (MOF), denoted as NU-1701, has been synthesized and crystallographically characterized. Density functional theory calculations highlight various possible electronic transitions that may present in NU-1701 . These transitions are competitive and indicate increased lanthanide character of Ce(iii ).